Enzymatic activity of three sugarcane varieties under salt stress - Mercia F. Carvalho; Marcus M. Correa; Gian C. Carvalho; Fernando C. Rolim Neto; Gessica P. A. Marinho; Sunamita B. de Andrade (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Sugarcane is a species of great economic importance to Brazil. The study of enzymatic activity has helped to identify varieties of sugarcane tolerant to salt stress, for planting in Brazilian semiarid regions, where there is the occurrence of saline soils. The objective of this study was to evaluate the enzymatic activity of three varieties of sugarcane subjected to stress caused by salinity. The experiment was conducted in a greenhouse at the Federal Rural University of Pernambuco, in a completely randomized design with four replicates. The leaf blade samples were collected for analysis of soluble proteins and determination of the activity of catalase and ascorbate peroxidase. The protein content was higher for RB962962 and lower for the varieties RB92579 and RB867515. However, in RB867515, there was an increase in the activity of ascorbate peroxidase and catalase, while the varieties RB92579 and RB962962 showed a reduction in the activity of these enzymes. These results indicate that the variety RB867515 has a more efficient mechanism in plant protection against the action of reactive oxygen species.